A taxonomic review of Korean Atheta Thomson subgenus Atheta Thomson (Coleoptera, Staphylinidae, Aleocharinae), with descriptions of two new species - Lee, Seung-Gyu; Ahn, Kee-Jeong (Zootaxa, 2019)
A taxonomic review of Atheta Thomson subgenus Atheta Thomson in the Korean Peninsula is presented. The subgenus is represented in Korea by eight species including two new species, A. (A.) prolixa Lee & Ahn, sp. nov. and A. (A.) vegrandis Lee & Ahn, sp. nov. Atheta (A.) sauteri Bernhauer is reported for the first time in South Korea. A key, descriptions, habitus photographs and illustrations of the diagnostic characters are provided.